Enhancing Interval Training in Competitive Swimming Through Interval Track Lighting: A Programmable Visual Pacing System - Hadi, Santika Rentika; Jumali, Muhammad Abdul; Haris, Abdul; Mardhika, Riga (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study introduces Interval Track Lighting (ITL), an innovative, programmable visual pacing system designed to enhance the efficacy of interval training among competitive swimmers. Despite interval training's recognized physiological benefits, its practical application in aquatic sports often suffers from imprecise pacing, reliance on verbal cues, and limited individualization. ITL addresses these challenges by providing real-time visual feedback via synchronized LED lights installed along the swimming lane, allowing swimmers to match their strokes to target time intervals set by coaches. This research employed a Research and Development (R&D) framework using the ADDIE model comprising analysis, design, development, implementation, and evaluation phases. A prototype was developed and tested over 14 training sessions involving eight age-group swimmers. The effectiveness of the ITL system was evaluated through a mixed-method approach combining pretest-posttest sprint performance, structured observations, interviews, and surveys. The results revealed a statistically significant improvement in 50-meter sprint times (mean improvement = 0.84 seconds; p = 0.014; Cohen’s d = 0.87), with swimmers reporting enhanced pacing accuracy and focus. Coaches highlighted ITL’s usability and contribution to reducing cognitive and logistical load during training. The findings suggest that ITL not only improves interval training outcomes but also fosters athlete autonomy and supports self-regulated learning. This study contributes to the growing field of technology-assisted sports training by offering a scalable, evidence-based solution for optimizing performance in swimming and potentially other time-regulated sports.